The Influence of Capital Structure, Liquidity, and Size on the Intrinsic Value of Property Companies - Silalahi, Daniel; Muda, Iskandar; Absah, Yeni (International Journal Labs, 2025)
This study investigates the influence of capital structure, liquidity, and firm size on the intrinsic value of property companies listed on the Indonesia Stock Exchange. The property and real estate sector plays a crucial role in Indonesia's economy, contributing significantly to the national GDP. However, challenges such as the COVID-19 pandemic and economic uncertainty have impacted the sector's performance. This research employs a quantitative approach, analyzing financial data from 13 property companies from 2019 to 2024. Utilizing multiple linear regression, the study finds that capital structure and liquidity positively affect profitability, which in turn enhances the intrinsic value of these firms. The results underscore the importance of effective financial management in supporting the intrinsic value of property companies.